2020
DOI: 10.1042/bsr20193939
|View full text |Cite
|
Sign up to set email alerts
|

Questing functions and structures of hypothetical proteins from Campylobacter jejuni: a computer-aided approach

Abstract: Campylobacter jejuni (C. jejuni) is considered to be one of the most frequent causes of bacterial gastroenteritis globally, especially in young children. The genome of C. jejuni contains many proteins with unknown functions termed as hypothetical proteins (HPs). These proteins might have essential biological role to show the full spectrum of this bacterium. Hence, our study aimed to determine the functions of HPs, pertaining to the genome of C. jejuni. An in-silico work flow integrating various tools were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…To determine the interaction partners of the HPs, we performed a protein-protein interaction analysis [ 72 ]. In this study, protein WP_095290960.1, RNA polymerase sporulation sigma factor SigK showed a very strong interaction (score 0.930) with the sporulation stage IV protein A (SpoIVA) which is involved in sporulation [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the interaction partners of the HPs, we performed a protein-protein interaction analysis [ 72 ]. In this study, protein WP_095290960.1, RNA polymerase sporulation sigma factor SigK showed a very strong interaction (score 0.930) with the sporulation stage IV protein A (SpoIVA) which is involved in sporulation [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Q8RGQ9 protein catalyzes ATP-dependent phosphorylation of 4-carbon acid sugars and nucleotides by binding them through N & C terminal domains respectively [61]. Q8RG53 and Q8RF83 contain a tetratricopeptide repeat and it has been identified that proteins with this repeat are involved in virulence related functions [6,62].…”
Section: Binding Proteinsmentioning
confidence: 99%
“…These previously uncharacterized proteins may yield interesting results and shed some light on functionality of a cell [5]. Many researchers have used this computer guided approach to functionally annotate the uncharacterized protein or HP from different organisms [6][7][8]. In the present study, we have attempted the functional annotation of uncharacterized proteins present in the genome of F. nucleatum strain ATCC 25586.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the interaction partners of the HPs, we performed a protein-protein interaction analysis (Gazi et al, 2020). In this study, protein WP_095290960.1, RNA polymerase sporulation sigma factor SigK showed a very strong interaction (score 0.930) with the sporulation stage IV protein A (spoIVA) which is involved in sporulation (Roels et al, 1992).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%